2003
DOI: 10.1074/jbc.m301554200
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-Methyl-d-aspartate Receptors in the Neuroprotective Activation of Extracellular Signal-regulated Kinase 1/2 by Cisplatin

Abstract: Neurons are exposed to damaging stimuli that can trigger cell death and subsequently cause serious neurological disorders. Therefore, it is important to define defense mechanisms that can be activated in response to damage to reduce neuronal loss. Here we report that cisplatin (CPDD), a neurotoxic anticancer drug that damages DNA, triggered apoptosis and activated the extracellular signal-regulated kinase 1/2 (ERK1/2) pathway in cultured rat cortical neurons. Inhibition of ERK1/2 activation using either pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…Caspase-3 activity was determined using a colorimetric assay (Promega) as described previously (Gozdz et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Caspase-3 activity was determined using a colorimetric assay (Promega) as described previously (Gozdz et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that in cortical neurons, which were treated with DNA-damaging drugs including CPT, BDNF suppresses apoptosis by activating the ERK1/2 pathway (Hetman et al, 1999;Gozdz et al, 2003). Others have shown that ERK1/2 mediates BDNF protection against TD (Bonni et al, 1999).…”
Section: Ksr1 Contributes To Antiapoptotic Effects Of Bdnfmentioning
confidence: 99%
See 1 more Smart Citation
“…As anticancer DNA-damaging cisplatin induces a prolonged activation of ERK1/2, whose outcomes on cell death/cell survival are cell-type dependent (Gozdz et al, 2003;Arany et al, 2004), we monitored ERK phosphorylation by western blot analysis during dose-response treatment of cisplatin on U87MG-expressing sense-and antisense-DUSP6 (Figure 4c). Immunoblot analysis showed that forced expression of DUSP6 was sufficient to inhibit phosphorylation of ERK, and increasing doses of cisplatin were not able to change it at all (as reported in U87MG DUSP6-infected cells).…”
Section: Dusp6 Regulation and Function In Glioblastoma Cancer Cells Smentioning
confidence: 99%
“…For example, by suppressing the activation of glycogen synthase kinase-3␤, low levels of NMDA receptor agonist protect cortical neurons from apoptosis because of phosphatidylinositol-3-kinase blockade (57). Treatment of cortical neurons with cisplatin, a neurotoxic antimitotic, triggers neuroprotective mechanisms by enhancing NMDA receptor activity and thus increasing ERK1͞2 signaling (58). Similarly, it has been demonstrated both in vivo and in cell culture that small ischemic events can trigger a NMDA receptordependent response that provides protection from subsequent larger ischemic events (59,60).…”
Section: Nmda Receptor-dependent Protection From Exogenous Challengementioning
confidence: 99%